Indonesian EFL Learners’ Willingness to Communicate Development: Stories from Informal Digital Learning of English - Nur Arifah Drajati; Sri Haryati; Dewi Rochsantiningsih; Ellisa Indriyani Putri Handayani; Dewi Cahyaningrum; Surya Agung Wijaya; Tyarakanita (Langkawi: Journal of The Association for Arabic and English, 2025)
EFL learners often hesitate to communicate in English, especially during in-class activities, because they fear making mistakes. In contrast, students active in IDLE activities are more willing to communicate in English. However, development processes beyond their willingness to communicate (WTC) in informal digital learning of English (IDLE) have not been sufficiently addressed. This study explored how Indonesian EFL learners develop their WTC in English from receptive- and productive-IDLE. This study employed a narrative study. To gain a deep understanding of the stories, we purposely recruited five university EFL learners who regularly practice IDLE. The data included learning diaries and in-depth interviews with stimulus recall. Our qualitative content analysis revealed that students who participated in fan practices initially engaged with WTC, influencing various factors, including the degree of acquaintance, formality of the situation, number of people present, topic of discussion, degree of evaluation, knowledge of the subject, language of discourse, and the language proficiencies of public figures. Our findings also conformed to the pyramid model of willingness to communicate based on students’ IDLE activities. As they gradually developed their confidence and English communication skills, it took a long time, during which some of them began in junior high school and continued their studies at university. Educators may consider explicit supports to tailor in-class and out-of-class IDLE activities, which provide more qualitative and quantitative exposure to the authentic use of English.